Signs and symbols - Nelson, Nigel (Wayland Hove, 1992)
The book Signs and Symbols by Nigel Nelson, illustrated by Tony De Saulles, published in 1993 by wayland. This 32-page hardcover is part of the "Communications" series and explores various forms of symbolic representation that surround us, such as flags, road signs, map symbols, logos, and smoke signals. The book is illustrated with full-color photographs and artwork throughout, providing readers with a visual understanding of these diverse symbols.